2015
DOI: 10.21283/2376905x.3.44
|View full text |Cite
|
Sign up to set email alerts
|

Spanish heritage language learners vs. L2 learners: What CAF reveals about written proficiency

Abstract: ENRecently, great interest has emerged in identifying the learning needs of heritage language (HL) learners. In comparing HL and second language (L2) learners, research suggests that L2 learners outperform HL learners when examining writing abilities (Montrul, 2010;Potowski, 2013). However, complexity, accuracy, and fluency (CAF) have been overlooked when examining HL learners' writing proficiency, and it could provide a better picture of their writing skills in a spontaneous untimed assignment. To address thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
0
8
1
1
Order By: Relevance
“…Xiao-Desai and Wong (2017) analyzed classroom blogs written by 266 HL students of Mandarin across four levels of the curriculum and found that their use of epistemic expressions, which are important in signaling writing stance (e.g., kěnéng, maybe; wǒ juéde, I feel or I think), increased rapidly in frequency of use at the initial levels and later remained stable in frequency but expanded greatly in diversity at the advanced levels. An advantage in writing was found by Camus and Adrada-Rafael (2015) for HL over FL students of Spanish on an untimed essay about the societal impact of smart phones. The essays written by HL students contained more subordination, fewer errors, and were longer overall than the essays written by FL students.…”
Section: The Variable Of Literacy In Hld Researchmentioning
confidence: 97%
“…Xiao-Desai and Wong (2017) analyzed classroom blogs written by 266 HL students of Mandarin across four levels of the curriculum and found that their use of epistemic expressions, which are important in signaling writing stance (e.g., kěnéng, maybe; wǒ juéde, I feel or I think), increased rapidly in frequency of use at the initial levels and later remained stable in frequency but expanded greatly in diversity at the advanced levels. An advantage in writing was found by Camus and Adrada-Rafael (2015) for HL over FL students of Spanish on an untimed essay about the societal impact of smart phones. The essays written by HL students contained more subordination, fewer errors, and were longer overall than the essays written by FL students.…”
Section: The Variable Of Literacy In Hld Researchmentioning
confidence: 97%
“…Most likely, this finding is due to the fact that the HL participants were just overall more proficient in Spanish than the L2 learners. However, Spicer-Escalante (2007) did not measure participants' proficiency, and Camus and Adrada (2015) only reported on HL participants' self-ratings of their proficiency level in Spanish and did not report on L2 participants' self-ratings nor did they include an objective measurement of proficiency. Even though participants in both studies were recruited from the same courses, it has been established in HL-L2 task-based studies that HL learners tend to be more proficient than their L2 peers when they are recruited from the same courses (Henshaw, 2015;Kim, Lee & Kim, 2018;Torres & Cung, 2019).…”
Section: Hl Writing Studies With Measures Of Accuracy and Syntactic C...mentioning
confidence: 99%
“…They are people that for one reason or the other have decided to take up a foreign language and who may or may not have formally enrolled in the educational system. Camus and Adrada-Rafael (2015), compare the writing abilities between heritage language speakers and L2 students. They suggest that proficient L2 learners possess conscious and mechanical knowledge of a language like rules, writing system, and a deep understanding of controlled and artificial contexts where the language can be used.…”
Section: The Studentmentioning
confidence: 99%